Memória de boiadeiro: a religiosidade no Centro de Umbanda Tupinambá - Vieira, Shirlene dos Passos (2012)
This work is to study the Umbanda Umbanda Tupinambá Center, trying to glimpse its presence in the formation of Umbanda Sertaneja North Mine, and consolidate it as a cultural element. Considering the social factor Clarence Hills, a frontier society that has suffered over the years the influence of the interpenetration of opposites trying to keep the loyalty of their initial training. It is intended to the study of memory and religion Umbanda Center Tupinambá unravel the relevance of these characteristics, highlighting the existence of strong women who will help comprise the hinterland and identity of the entity to determine the uniqueness of the ethos Cattle backcountry. Throughout its existence the Centre believed to reveal characteristics inherited from its founder Northeastern Ilizario as a rhythmic Umbanda the yard. And there is this kind of Umbanda, from Bahia features that makes it different from others. One of these differences is to preserve the collective memory of the group that preserves lines opened by their parents who are still active today. Within this training we can see the result of preservation in this group that preserves the view of patrons stay of proceedings of worship and rituals